2020
DOI: 10.1186/s12893-020-00893-7
|View full text |Cite
|
Sign up to set email alerts
|

Odontoid fractures: impact of age and comorbidities on surgical decision making

Abstract: Background Surgical fixation is recommended for type II and III odontoid fractures (OFx) with major translation of the odontoid fragment, regardless of the patient’s age, and for all type II OFx in patients aged ≥50 years. The level of compliance with this recommendation is unknown, and our hypothesis is that open surgical fixation is less frequently performed than recommended. We suspect that this discrepancy might be due to the older age and comorbidities among patients with OFx. Methods We present a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
3
19
1
6
Order By: Relevance
“…The level of CS-Fx was C0 -C2 in 38%, C3 -C7 in 55%, and both C0 -C2 and C3 -C7 in 7%. The most frequent Fx in the upper cervical spine was C2 odontoid Fx (the most common Fx in the elderly), which is in line with other reports [3,22]. The most frequent C3 -C7 (subaxial)…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The level of CS-Fx was C0 -C2 in 38%, C3 -C7 in 55%, and both C0 -C2 and C3 -C7 in 7%. The most frequent Fx in the upper cervical spine was C2 odontoid Fx (the most common Fx in the elderly), which is in line with other reports [3,22]. The most frequent C3 -C7 (subaxial)…”
Section: Discussionsupporting
confidence: 91%
“…Surgical xation has previously been recommended for type II odontoid fractures. We have recently documented that most of these patients can be managed with external immobilization alone, thereby avoiding a surgical procedure associated with high risk in frail older people [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have challenged the recommendation of surgical fixation of almost all type II OFx and indicated that fibrous/nonbony fusion can be a satisfactory outcome in frail elderly patients [8,9,14,29]. Among our patients available for long-term follow-up, 39% had bony fusion, 57% had fibrous union, and only 4% had pseudarthrosis.…”
Section: Of 27mentioning
confidence: 84%
“…We have recently shown that primary surgical fixation of type II OFx was only performed in 33% of our patients in the 4-year time period 2015 -2018 [14]. The reasons given for choosing primary external immobilization instead of primary surgical fixation for these patients were a combination of age and comorbidity in 88%, nonsurvivable injury in 6% and delayed diagnosis in 6%.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation